Assessment of endocrine-disrupting effects of emerging polyhalogenated carbazoles (PHCZs): In vitro, in silico, and in vivo evidence. (July 2020) - Yue, Siqing; Zhang, Ting; Shen, Qiqi; Song, Qin; Ji, Chenyang; Chen, Yuanchen; Mao, Manfei; Kong, Yuan; Chen, Da; Liu, Jing; Sun, Zhe; Zhao, Meirong
Graphical abstract: Highlights: First evaluation of the endocrine disruption of emerging PHCZs. ERα agonistic potency was evidenced by in vitro, in vivo, and in silico . E2 levels were also elevated following certain PHCZs exposure. GRα antagonistic activities were also observed. Abstract: Polyhalogenated carbazoles (PHCZs) are an emerging class of persistent, bioaccumulative compounds that are structurally and chemically related to dioxins. They have been detected widely in sediment, river, and soil samples, but their environmental risks are largely unknown. Therefore, seven common PHCZs were tested for their endocrine disrupting potential in silico, in vitro, and in vivo . A dual-luciferase reporter gene assay was used to detect receptor-mediated (agonist or antagonistic) activity (concentration range: 10 −9 –10 −5 M) against the estrogen receptor α (ERα), glucocorticoid receptor α (GRα), and mineralocorticoid receptor (MR). The alterations in the steroidogenesis pathway were investigated in H295R cells. Antagonistic effects against GRα were observed with five PHCZs, along with an increase in the cortisol levels of H295R cells. The most common effect observed was that of the agonistic activity of ERα, with the molecular docking analysis further indicating that hydrogen bonding and hydrophobic interactions may stabilize the interaction between PHCZs and the estrogen receptor binding pocket. In addition, a seven-day exposure of young female rats to three PHCZs (27-BCZ, 3-BCZ, and 36-BCZ) resulted in changes in serum E2 levels, uterine epithelium cell heights, and relative uterus weights. In conclusion, endocrine-disrupting effects, especially the estrogenic effects, were observed for the tested PHCZs. Such adverse effects of PHCZs on humans and wildlife warrant further thorough investigation.